2021
DOI: 10.1186/s12931-021-01903-9
|View full text |Cite
|
Sign up to set email alerts
|

Airway IL-1β associates with IL-5 production following dust mite allergen inhalation in humans

Abstract: Background Preclinical studies implicate interleukin (IL)-1β as a key mediator of asthma and have shown the efficacy of IL-1 antagonism for treatment of allergic airway inflammation; human studies in this area are lacking. Objectives Our aim was to study the relationship of airway IL-1β to features of acute allergen-induced asthma exacerbation in humans. Methods Dust mite-allergic adults with mild asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Although IL-1 is mainly considered as proinflammatory cytokine, one recent study showed an increased production of IL-1β after allergen challenge in asthmatics and prechallenge concentration was correlated with blood eosinophilia and FeNO. 4 Therefore, elevation of the IL-1ra observed in our study may be a reflect of regulatory mechanisms initiated by ani-IL-5 therapy.…”
Section: Cytokines In Serum Nasal Secretion and Exhaled Breath Conden...mentioning
confidence: 53%
“…Although IL-1 is mainly considered as proinflammatory cytokine, one recent study showed an increased production of IL-1β after allergen challenge in asthmatics and prechallenge concentration was correlated with blood eosinophilia and FeNO. 4 Therefore, elevation of the IL-1ra observed in our study may be a reflect of regulatory mechanisms initiated by ani-IL-5 therapy.…”
Section: Cytokines In Serum Nasal Secretion and Exhaled Breath Conden...mentioning
confidence: 53%